Description and ontogeny of Pattersoncypris minima sp. nov. (Crustacea: Ostracoda), Araripe Basin, Northeast Brazil - de Almeida-Lima, Débora Soares; Piovesan, Enelise Katia; Sayão, Juliana Manso; de Lima, Flaviana Jorge (Zootaxa, 2020)
Representatives of the Class Ostracoda are widely used as tools in applied paleoecological and biostratigraphical studies in all continents. In the Araripe Basin, located in the northeastern of Brazil, the Romualdo Formation is one of the most studied, not only for the preservation but also for the abundance of its fossils. The ostracod genus Pattersoncypris Bate, 1972 is well-represented in this formation and it is the most abundant, which reinforces the importance of its taxonomic study. In this work, Pattersoncypris minima sp. nov. is described for the Romualdo Formation as a contribution to the knowledge on Brazilian Cretaceous non-marine ostracods. Taphonomic aspects are also presented, considering the complete ontogenetic stages of the material.